The Effect of Human Capital Inequality on Income Inequality: Evidence from Indonesia: An Application of Generalized Method of Moment Estimation - Hafizh Meyzar Aqil; Dwi Wahyuniati (Politeknik Statistika STIS, 2021)
Education inequality in Indonesia tends to experience a downward trend which indicates that the education distribution is more equally distributed from year to year. this phenomenon should lead to a reduction in income inequality. However, income inequality in Indonesia has increased compared to 9 years ago. This study intends to look at the human capital inequality condition in provinces in Indonesia and analyze the effect of human capital inequality on income inequality. The Gini coefficient concept is used to measure human capital inequality and income inequality. The annual panel data covered 34 provinces in Indonesia from 2015 – 2019. The analytical methods used dynamic panel data regression using the Generalized Method of Moment (GMM) Arellano-Bond approach. The results indicate income inequality with a lag of 1 year, literacy rate, and trade openness have a negative and significant effect on income inequality. Furthermore, the human capital inequality and the average years of schooling have a positive and significant effect on income inequality. So, to reduce income inequality, policymakers are advised to minimize human capital inequality, especially in the education sector by paying attention to conditions in priority provinces.